On the democratic constant of Haar subsystems in L_1 [0,1]^d - Srapionyan, Nerses (Armenian Journal of Mathematics, 2019)
In this paper, we estimate the democratic constant for the democratic subsystems of the d-dimensional Haar system in L_1[0,1]^d.